Attracting women into male-dominated trades: Views of young women in Australia - Karen Struthers; Glenda Strachan (International Journal for Research in Vocational Education and Training (IJRVET), 2019)
Context: The persistent low female participation in male-dominated trades is not attracting a high level of public attention and policy action. There are determined, yet adhoc actions by advocates in response to evidence that economic benefits will be derived for industry and women through increased female participation in the male-dominated trades. Occupational segregation of the trades remains resistant to change. Methods: To better understand the barriers limiting female participation in the male-dominated trades from the perspective of young women, this PhD study features interviews with female secondary students, complemented by interviews with industry stakeholders and a quantitative analysis of VET and trade participation data. The three primary research questions are: 1) What is the extent of gender segregation in vocational education and training (VET) and typically male-dominated trades in Australia, and how does this compare internationally? 2) Why do very few female students choose male-dominated trades as their job pathway? 3) What can be done, particularly in the education and training sectors, to increase female interest in, and take-up of, the male-dominated trades? Findings: The results of this research showed that the composition of trade-qualified females in male-dominated trades is persistently low at 2-3%. The views of young women affirmed the evidence showing system-wide barriers limit female interest in these trades. Most influential is that gender stereotypes of work are set by Year 10 and that female enrolment in Maths (a pre-requisite for male-dominated careers) is low; these trades are seen as 'jobs for the boys who don't do academic,' and the fear of intimidation and harassment deters young women. Low enrolment of female students in male-dominated trade courses indicates that this entrenched occupational segregation of the trades will remain resistant to change for some time to come. Conclusion: The findings indicate that ad hoc responses to overcome gender segregation of the trades is not effective. Influenced by systems theory and a social ecological model (SEM) of change, the researchers promote the need for sustained, nation-wide awareness and action involving VET and school sectors, industry, government and trade unions to attract more women into male-dominated trades.
Keywords: 330; Vocational Education and Training; Non-traditional Occupations; Women in Trades; VET